Pulse Reshaping by the Two-port Nonlinear Fiber Mach-Zehnder Interferometer - Quy, Ho Quang; Hoa, Nguyen Van; Tam, Nguyen Thi Thanh (Communications in Physics, 2011)
In this article, the reshaping of the series of sinuous pulses and Gaussian pulses with arbitrary amplitude of laser signal by two-port nonlinear fiber Mach-Zehnder interferometer are simulated. The output series of close to flat-form pulses of laser signal is obtained. The influence of the input intensity, length of the nonlinear fiber, and nonlinear coefficient of refractive index on the shape of output pulse is discussed.